1998
DOI: 10.1046/j.1365-313x.1998.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin‐photoaffinity labelling of two polypeptides in plant plasma membranes

Abstract: SummaryTwo polypeptides of M r 68 kDa and 18 kDa were gibberellin (GA)-photoaffinity labelled in vitro in plasma membrane preparations from oat (Avena sativa L.) aleurone and from leaves and stems of wild-type and GA-sensitivity mutants of different species. Labelling of these polypeptides could be competed by biologically active, but not by inactive, GAs, indicating the likely biological significance of these interactions. On 2-dimensional gels the radiolabelled polypeptides were each resolved as one intensel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Analysis of gene expression during the conversion of inactive GA to active GA, and using mutants defective in shoots and scutella formation, revealed that the scutella region of the embryo is essential for the induction of alpha-amylase [78]. Studies suggest that GA is perceived in the plasma membrane by gibberellin-binding protein (GBP) [79,80,81,82] and inside the cell by GID1 [83]. However, Kenji et al [83] showed that GBP does not exist and that the GID1-DELLA system is solely responsible for GA reception in rice aleurone cells using a gid1 mutant.…”
Section: Regulation Of Alpha-amylase Expressionmentioning
confidence: 99%
“…Analysis of gene expression during the conversion of inactive GA to active GA, and using mutants defective in shoots and scutella formation, revealed that the scutella region of the embryo is essential for the induction of alpha-amylase [78]. Studies suggest that GA is perceived in the plasma membrane by gibberellin-binding protein (GBP) [79,80,81,82] and inside the cell by GID1 [83]. However, Kenji et al [83] showed that GBP does not exist and that the GID1-DELLA system is solely responsible for GA reception in rice aleurone cells using a gid1 mutant.…”
Section: Regulation Of Alpha-amylase Expressionmentioning
confidence: 99%
“…Based on these observations, Hooley and his colleagues attempted to identify a GA receptor located on the plasma membrane of oat aleurone cells using a photoaffinitylabeled GA, and succeeded in detecting two GBPs: a 60-kDa protein localized in the microsomal fraction (20), and a 50-kDa protein in the cytosolic fraction (19,72). Two other GBPs of 68/18 kDa were also detected in the plasma membrane fraction from oat aleurone by the same photoaffinity-labeling method (39). Even though partial amino acid sequences for the 18-kDa GBP have been identified, there is no further information about these GBPs.…”
Section: Biochemical Search For the Gibberellin Receptormentioning
confidence: 99%
“…Although several GA‐binding proteins have been identified from different plants including maize (Keith & Rappaport 1987), bean (Nakajima et al . 1997), rice (Komatsu, Matsuda & Hirano 1996b), oat, pea and Arabidopsis (Lovegrove et al . 1998), their functions remain to be identified.…”
Section: Introductionmentioning
confidence: 99%